Why garden? – Attitudes and the perceived health benefits of home gardening. (May 2021) - Chalmin-Pui, Lauriane Suyin; Griffiths, Alistair; Roe, Jenny; Heaton, Timothy; Cameron, Ross
Abstract: Domestic (home) gardens provide opportunities for psychological and physical health benefits, yet these environments have received less attention in terms of their therapeutic value compared to other urban green spaces. This is despite their ubiquity and the popularity of gardening as a pastime. This research explored why residents engaged with gardening and the extent to which they recognised any health benefits from the activity. A questionnaire was distributed electronically within the UK, with 5766 gardeners and 249 non-gardeners responding. Data were collated on factors including garden typology, frequency of gardening and individual perceptions of health and well-being. Significant associations were found between improvements in well-being, perceived stress and physical activity and more frequent gardening. Gardening on a frequent basis i.e. at least 2–3 times a week, corresponded with greatest perceived health benefits. Improving health, however, was not the prime motivator to garden, but rather the direct pleasure gardening brought to the participants. There was evidence that satisfaction with one's front garden and the time spent in it increased as the proportion of vegetation was enhanced. The data supports the notion that domestic gardens should be given greater prominence in urban planning debates, due to the role they play in providing health benefits. Highlights: An increased frequency of gardening correlated with health benefits Gardening at least two to three times a week maximised the benefits. Pleasure though, not health, was the prime motivator to garden. People with existing health issues particularly acknowledged the value of gardening. Satisfaction/engagement improved as amount of green space increased in gardens.